Prototipo de edificio de oficinas saludables en el centro de Medellín (2020)
Sick building syndrome is a phenomenon in which the physical, chemical, biological, and psychosocial factors of a building can affect the health of its occupants. This research starts from the study of this syndrome and its possible presence in Medellín, emphasizing the office buildings located downtown.The study of these buildings has the purpose of determining the presence of the syndrome with its different factors, to propose a healthy office building model of the buildings that already exist, as well as an architectural proposal for a new office building, all along with a proposal to improve the social, economic and environmental dynamics of the city center.